2010
DOI: 10.1002/cncr.25261
|View full text |Cite
|
Sign up to set email alerts
|

BRAF, a target in melanoma

Abstract: The successful translation of therapies targeting signal-transduction pathways that are activated by oncogenes has provided a model for molecularly targeted therapy, and the identification of mutations in v-raf murine sarcoma viral oncogene homolog B1 (BRAF), a serine/threonine kinase, has turned the attention of the melanoma field toward this concept. The current review indicated that BRAF represents an important target in cancer, in part because it is present in 7% of all cancers and also because it represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(49 citation statements)
references
References 82 publications
2
47
0
Order By: Relevance
“…This mutation is activating in melanoma and confers sensitivity to BRAF inhibition. 42 To our knowledge, this mutation has not been described in CLL prior to this report. Further studies assessing the role of BRAF inhibitors in patients with CLL who harbor BRAF mutations are warranted.…”
Section: Discussionmentioning
confidence: 64%
“…This mutation is activating in melanoma and confers sensitivity to BRAF inhibition. 42 To our knowledge, this mutation has not been described in CLL prior to this report. Further studies assessing the role of BRAF inhibitors in patients with CLL who harbor BRAF mutations are warranted.…”
Section: Discussionmentioning
confidence: 64%
“…BRAF is mutated in approximately 50% of melanomas; 80ā€“90% of these activating mutations involve a single substitution of valine in position 600 with glutamic acid (V600E) (18). Additional, more rare, BRAF mutations include V600K (valine substituted with lysine) and V600D (valine substituted with aspartic acid) (19).…”
Section: Molecular Aspects Of Melanoma Development and Progressionmentioning
confidence: 99%
“…In melanoma is estimated that the prevalence of BRAF mutation is between 30% and 70%. The most common BRAF mutation is the T1796A point mutation, that results in a substitution of glutamic acid (E) for valine (V) at position 600 of the aminoacid sequence in exon 15 while the other mutations observed, like the ''V600E'' substitution, interest the kinase domain of the protein [72]. This mutation introduces, in the kinase domain, a conformational change in protein structure, leading to protein constitutive activation and increase of its basal kinase activity [1].…”
Section: Ras/raf/mek/erkmentioning
confidence: 99%
“…It has also been shown that BRAF mutations lead to the activation of the MAP kinase pathway in a way independent Ras. NRAS and BRAF mutations are mutually exclusive [72]. The MAP kinase signaling pathway activation is an obligatory step for the melanocytes transformations induction.…”
Section: Ras/raf/mek/erkmentioning
confidence: 99%